Evaluation of an Audio Mode of the Automated Medical History - Stead, W. W.; Hammond, W. E.; Estes, E. H. (Methods of Information in Medicine, 1977)
The Westinghouse Voice Response System is a stand-alone hardware unit designed for automated data collection. Questions are asked in the audio mode. Responses are printed at the time of the interview and stored on magnetic tape for future retrieval. This audio system was evaluated as a method for the collection of the initial medical history. In addition, comparisons were made among three techniques of automated data collection: audio, video and paper and pencil. The audio mode of automated history taking was more effective than comparable paper and pencil and video systems in situations where the patient population was of borderline literacy. The Westinghouse Voice Response System is a viable stand-alone system for those situations in which on-line access to a computer is not available.
Keywords: Automated History; Audio Questionnaire; Comparison of History Collection Mode